On the dualistic unity of natural science and the humanities. - Safontseva, Natalia (SHS Web of Conferences, 2023)
This paper is an analysis of the effectiveness of the Russian learners from the 2019 TIMSS International Monitoring Study report. While analyzing the document, the initial conclusion drawn by the author is that the mathematical and natural science literacy of Russian schoolchildren is quite high and that the educational system in Russia is stable. At the same time, the author suggests that rethinking the directions of educational development is impossible without taking into account the underlying processes occurring in the depths of basic general education. In the author's opinion, the lack of significant gains in the scores of Russian students over the last 2 phases of the TIMSS studies is an indicator of certain stagnation in primary mathematics and science education. The author is of the belief that a statement of this fact should contribute to the fundamentalism of education. Assessing the structural correlation between natural science and humanities knowledge by quantitative volume of academic load of mathematics and natural science disciplines, the author points to the dualistic unity of natural science and humanities knowledge in high school, which should contribute to the development of creative independent thinking of students. The author's understanding of the results of the context survey of Russian schoolchildren indicates the need to improve the professional expertise of the science teachers, which will improve the outcome of the educational process. The author suggests adopting the experience of other countries in implementing the interdisciplinary approach to the educational process. The author emphasizes that STEM education imposes special requirements on the teacher, who must have integrated knowledge of mathematics, science and technology, be fluent in computer programs, be motivated to work with children and be skilled in didactics.